1998
DOI: 10.1203/00006450-199803000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Cord Blood Leptin: Its Relationship to Birth Weight, Body Mass Index, Maternal Diabetes, and Steroids

Abstract: Leptin is a 16-kD protein encoded by the ob/ob (obesity) gene. In rodents it plays a role in obesity, diabetes, fertility, and neuroendocrine function. In humans serum concentrations of leptin correlate with total body fat in both adults and children. We measured cord blood leptin in 186 neonates that included 82 appropriate for gestational age (AGA), 47 large for gestational age (LGA), 20 infants of diabetic mothers, 52 preterm infants, and 15 intrauterine growth-retarded (IUGR) infants. There were 16 pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
104
6
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 45 publications
16
104
6
4
Order By: Relevance
“…Interestingly, the studies showing this sexual dimorphism were performed exclusively in FTN (19,22), whereas it was not found when the studied cohort included PTN (18). Our findings confirm both observations, with no differences in leptin levels found between sexes when the cohort was analyzed as a whole or in PTN separately, but with female FTN having higher leptin and free leptin index than male FTN.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, the studies showing this sexual dimorphism were performed exclusively in FTN (19,22), whereas it was not found when the studied cohort included PTN (18). Our findings confirm both observations, with no differences in leptin levels found between sexes when the cohort was analyzed as a whole or in PTN separately, but with female FTN having higher leptin and free leptin index than male FTN.…”
Section: Discussionsupporting
confidence: 81%
“…The increase in leptin levels with the progression of gestation has been postulated as a direct effect of advancing gestational age (16,17); nevertheless, it is thought to be mainly due to the quantitative increase in AT acquisition by the fetus throughout pregnancy (18)(19)(20), which is supported by the lower leptin levels and free leptin index found in SGA newborns, as by the positive correlation of leptin levels and free leptin index with birth weight, independently of gestational age (whereas their correlations with gestational age disappeared when controlling for birth weight). Hence, leptin levels may be a better indicator of the amount of AT in the newborn rather than of its level of maturation, as previously suggested (21).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cord blood leptin levels are elevated in infants of diabetic mothers and in largefor-gestational-age newborns [130]. However, whether increased leptin production is due to increased fetal fat mass [147,148] or others factors could affect adipose tissue in the fetus remain unclear, and further investigations regarding the feto-maternal leptinemia are necessary to clarity this point [149,150].…”
Section: Role Of Leptin In Fetal Developmentmentioning
confidence: 99%
“…Leptin is a 167-amino-acid peptide primarily expressed in adipose tissue (Zhang et al, 1994), but also produced by the stomach (Cinti et al, 2001), placenta (Masuzaki et al, 1997) and mammary epithelial cells (Smith-Kirwin et al, 1998), and it has been found in the cord blood of newborns (Shekhawat et al, 1998). Leptin exerts pleiotropic effects by binding and activating specific receptors, in particular in the arcuate nucleus in the hypothalamus, where it contributes to the control of energy homeostasis, by reducing food intake and increasing energy expenditure (Faroooqi and O'Rahilly, 2009).…”
Section: Introductionmentioning
confidence: 99%